Ulos Sustainability Towards Green Brands to Improve Marketing Performance Based on a Co-Creation Solution - Mariana Simanjuntak; Santi Agustina Manalu (Business Management Analysis Journal (BMAJ), 2022)
The purpose of this research is to produce ulos revitalization and create added value for the green sustainability of ulos production, oriented branding and its marketing so as to increase the life force of weavers and micro-entrepreneurs. Respondents are weavers and training entrepreneurs of ulos, retailers with a total of 316 people engaged in the production and service of Ulos production. Data collection was conducted by survey methods and questionnaires with statements used on a scale of 1-10. Data processing results with SEM AMOS show that green sustainability of Ulos oriented branding (GSB) proved unable to mediate between Product Innovation (PDI), Process Innovation (PCI) and Marketing Performance (MPF). In other words, green sustainability does not directly prove an improvement in marketing performance. GSG shows that it is able to improve Order Management (OMG). The process emphasizes on the relevance of green sustainability, it can be seen that PDI and PCI are proven to improve GSB. Sustainability of green branding can only be achieved when there is product and process innovation. SDL demonstrates the need for the development of new service innovations by investigating the prerequisites and general principles for developing sustainability. Dominant logic treats services as a category of market offerings to be developed and managed like ulos products. The concept of service design has been developed referring to a subset of "green" processes associated with rendering activities to define a concept, structure, or service infrastructure. This research invites ulos observers to understand the values of Ulos authenticity and its culture in sustainable entrepreneurship, inviting weavers and entrepreneurs to have prosocial motives that influence their interest in sustainable ulos entrepreneurship and the role of academia in promoting sustainable entrepreneurial practices.